Us and them? A study of an assessment system for higher education from the perspective of international students - Vitéz, Kitti (Autonomy and Responsibility Journal of Educational Sciences, 2022)
Book review: Aneta Hayes (2019). Inclusion, Epistemic Democracy and International Students. The Teaching Excellence Framework and Educational Policy. Keele University. Keele, Staffordshire, UK